Less is More/More Diverse: On The Communicative Utility of Linguistic Conventionalization - Teich, Elke; Fankhauser, Peter; Degaetano-Ortlieb, Stefania; Bizzoni, Yuri (Frontiers in Communication, 2021)
We present empirical evidence of the communicative utility of CONVENTIONALIZATION, i.e. convergence in linguistic usage over time, and DIVERSIFICATION, i.e. linguistic items acquiring different, more specific usages/meanings. From a diachronic perspective, conventionalization plays a crucial role in language change as a condition for innovation and grammaticalization (Bybee (2010); Schmid (2015)) and diversification is a cornerstone in the formation of sublanguages/registers, i.e. functional linguistic varieties (Halliday (1988); Harris (1991)). While it is widely acknowledged that change in language use is primarily socio-culturally determined pushing towards greater linguistic expressivity, we here highlight the limiting function of communicative concerns on diachronic linguistic variation showing that conventionalization and diversification are associated with a reduction of linguistic variability. To observe effects of linguistic variability reduction, we first need a well-defined notion of choice in context. Linguistically, this implies the paradigmatic axis of linguistic organization, i.e. the sets of linguistic options available in a given or similar syntagmatic contexts. Here, we draw on word embeddings, weakly neural distributional language models that have recently been employed to model semantic change and allow us to approximate the notion of paradigm by neighbourhood in vector space. Second, we need to capture changes in paradigmatic variability, i.e. reduction/expansion of linguistic options in a given context. As a formal index of paradigmatic variability we use entropy, which measures the contribution of linguistic units (e.g. words) in predicting linguistic choice in bits of information. Using entropy provides us with a link to a communicative interpretation, as it is a well-established measure of communicative efficiency with implications for cognitive processing (Linzen and Jaeger (2016); Venhuizen et al. (2019)); also, entropy is negatively correlated with distance in (word embedding) spaces which in turn shows cognitive reflexes in certain language processing tasks (Mitchell et al. (2008); Auguste et al. (2017)). In terms of domain we focus on science, looking at the diachronic development of scientific English from the 17th century to modern time. This provides us with a fairly constrained yet dynamic domain of discourse that has witnessed a powerful systematization throughout the centuries and developed specific linguistic conventions geared towards efficient communication.